2021
DOI: 10.3390/min11070707
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Organoclays Based on Clay Minerals with Different Structural Expansion Capacities

Abstract: An important goal in environmental research for industrial activity and sites is the investigation and development of effective adsorbents for chemical pollutants that are widespread, inexpensive, unharmful to the environment, and have the required adsorption selectivity. Organoclays are adsorption materials that can be obtained by modifying clays and clay minerals with various organic compounds through intercalation and surface grafting. Organoclays have important practical applications as adsorbents of a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 78 publications
0
6
0
1
Order By: Relevance
“…After organic modification, the layer spacing of bentonite increases, which increases the storage space in the layer and, finally, increases the adsorption capacity for organic pollutants [26]. The experimental results show that, after organic modification of natural bentonite, the expansivity and compressibility of OMB are both reduced [27]. Furthermore, the length of carbon chain of surfactants is also an important factor affecting the structure and properties of OMB.…”
Section: Introductionmentioning
confidence: 99%
“…After organic modification, the layer spacing of bentonite increases, which increases the storage space in the layer and, finally, increases the adsorption capacity for organic pollutants [26]. The experimental results show that, after organic modification of natural bentonite, the expansivity and compressibility of OMB are both reduced [27]. Furthermore, the length of carbon chain of surfactants is also an important factor affecting the structure and properties of OMB.…”
Section: Introductionmentioning
confidence: 99%
“…Clays are fine-grained materials composed of clay minerals, which are hydrated alumino-silicates belonging to the mineral groups of kaolin, smectite, palygorskite, sepiolite, illite, chlorite, and mixed-layered clays (Aghris et al 2021, Perelomov et al 2021, Belghazdis and Hachem 2022. Fireclay, which is one of the most popular refractories, is a type of clay that belongs to the aluminosilicate group of refractory materials and is extensively applied in the ceramics industry due to its high fusion temperatures (Antonovi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the affinity between nanoclays and the polymeric matrix, a naturally hydrophilic silicate surface could be rendered organophilic by implementing organic cations on the surface of the layers [9]. Many studies have found that adding reactive functional groups to the organic modifier further enhances compatibility in the nanocomposite system.…”
Section: Introductionmentioning
confidence: 99%